ChemInform Abstract: [Ge2]4‐ Dumbbells with Very Short Ge—Ge Distances in the Zintl Phase Li3NaGe2: A Solid‐State Equivalent to Molecular O2. Issue 13 (March 2016) - Scherf, Lavinia M.; Karttunen, Antti J.; Pecher, Oliver; Magusin, Pieter C. M. M.; Grey, Clare P.; Faessler, Thomas F.
Abstract: The novel ternary Zintl phase Li3 NaGe2 is prepared by heating a stoichiometric mixture of the elements (Ta ampoule in evacuated silica tubes, 400 °C, 7 d; cooling at a rate of 0.5 °C/min).